Advancing a climate smart strategy for biodiversity conservation in protected areas on the Qinghai-Xizang Plateau - Xuan Li; Yanzheng Yang; Pengxiang Zhao; Da Lv; Jun Zhao; Zijian Lu; Ping Huang; Jingyi Zhu; Hao Song; Binqiang Bao; Jalal Kassout; Ruonan Li; et al. (Geography and Sustainability)
The Qinghai-Xizang Plateau serves as an extensive gene pool for plateau species and a crucial focal point for global biodiversity conservation. Being a climate-sensitive region, the impacts of climate change have led to habitat loss, population extinction, and ecological imbalances, posing formidable challenges to the sustained effectiveness of existing protected areas. Despite substantial advancements in understanding species distribution, assessing habitat changes, and evaluating the efficiency of protected areas in recent decades, comprehensive evaluations encompassing all protected species are lacking, impeding conservation strategies. In this study, we gathered 137,856 observations, encompassing 2,605 species, and utilized the MaxEnt model to simulate changes in the current distribution patterns of endangered species and suitable habitats under future scenarios. We further proposed a climate smart approach to optimize the boundaries of protected areas in response to climate change. Key findings indicate that (1) the Qinghai-Xizang Plateau harbors 2,605 endangered species, constituting 34.04 % of the total endangered species catalog in China; (2) current high-adaptation habitats of Qinghai-Xizang Plateau cover a mere 7 % of the plateau, showing minimal alteration in protected efficiency under climate change scenarios (0.50 % increase); (3) incorporating the effects of climate change in adjusting protected area boundaries enhances their efficiency by an average of 20.52 %. Our proposed methodology holds promise for safeguarding endangered species on the Qinghai-Xizang Plateau and offers significant implications for analogous regions worldwide.